2023
DOI: 10.1111/jnp.12305
|View full text |Cite|
|
Sign up to set email alerts
|

Lesion‐symptom mapping of language impairments in people with brain tumours: The influence of linguistic stimuli

Abstract: People with tumours in specific brain sites might face difficulties in tasks with different linguistic material. Previous lesion-symptom mapping studies (VLSM) demonstrated that people with tumours in posterior temporal regions have more severe linguistic impairments. However, to the best of our knowledge, preoperative performance and lesion location on tasks with different linguistic stimuli have not been examined. In the present study, we performed VLSM on 52 people with left gliomas to examine whether tumou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…Salillas et al (2023) used verb generation during magnetoencephalography and showed larger neuronal responses in the inferior frontal gyrus with a condition with multiple correct responses (e.g., for a noun like 'button' there can be more than one correct response: 'to button up' and 'to sew'). Ntemou et al (2023) performed a voxel-lesion symptom mapping study based on 52 German speakers with left hemisphere gliomas and showed that, before surgery, tasks other than single-word naming (e.g., compound and sentence production) relate to further cortico-subcortical brain areas. Burkhardt et al (2023) showed that three French-speaking people with a left anterior tumour affecting the left inferior longitudinal fasciculus had difficulties retrieving the names of famous people, particularly after tumour removal surgery.…”
Section: Introduction To the Special Issue On Cognitive Neurosurgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Salillas et al (2023) used verb generation during magnetoencephalography and showed larger neuronal responses in the inferior frontal gyrus with a condition with multiple correct responses (e.g., for a noun like 'button' there can be more than one correct response: 'to button up' and 'to sew'). Ntemou et al (2023) performed a voxel-lesion symptom mapping study based on 52 German speakers with left hemisphere gliomas and showed that, before surgery, tasks other than single-word naming (e.g., compound and sentence production) relate to further cortico-subcortical brain areas. Burkhardt et al (2023) showed that three French-speaking people with a left anterior tumour affecting the left inferior longitudinal fasciculus had difficulties retrieving the names of famous people, particularly after tumour removal surgery.…”
Section: Introduction To the Special Issue On Cognitive Neurosurgerymentioning
confidence: 99%
“…Ntemou et al. (2023) performed a voxel‐lesion symptom mapping study based on 52 German speakers with left hemisphere gliomas and showed that, before surgery, tasks other than single‐word naming (e.g., compound and sentence production) relate to further cortico‐subcortical brain areas. Burkhardt et al.…”
mentioning
confidence: 99%